If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + -2 = 11 Reorder the terms: -2 + b = 11 Solving -2 + b = 11 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + b = 11 + 2 Combine like terms: -2 + 2 = 0 0 + b = 11 + 2 b = 11 + 2 Combine like terms: 11 + 2 = 13 b = 13 Simplifying b = 13
| 5x=-5x+10 | | 3-4q=-5+8q | | 7y^3+5y^2= | | -4(t-3)-2(7t-8)=9(t+2)+4 | | 11x-2y+12w-6y-2w+2x= | | 9h+7-6h=-5+9 | | 6-2(3x-2)=14 | | 1/2(w+1)=9 | | 6a^2x^2+11a^2x+4a^2= | | 4v-2(3-v)=-13 | | 14-y=5 | | 4(b-1)=-4+b | | 5x-(2x-2)=x+(3x-5) | | 5x-6=2x+21 | | 49-2x=7x+17 | | 19-(2x-2)=5 | | 5-2x=-4x(2x+1) | | 5-9x=55-23x | | (3/15)y+15=0 | | 0.5x^2+0.375x+2=0 | | 6x-4=13x-56 | | -0.2x+0.5x+7=1 | | 8y+4=24-4 | | (x+5)=7 | | -0.3x+0.2x-3=7 | | 4y-2=-20y | | 5x^2+8x-13=35-26x | | 4x+y=30 | | 5(90-7)=x-126 | | 7x^2+8x-13=43-33x | | 8x-3=-7 | | 4*-12=-5*+51 |